2013
DOI: 10.1111/dme.12120
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of postprandial endothelial dysfunction by spice mix added to high‐fat hamburger meat in men with Type 2 diabetes mellitus

Abstract: Adding a spice mix to hamburger meat prior to cooking resulted in a reduction in urinary malondialdehyde, an increase in urinary nitrate/nitrite and improvement of postprandial endothelial dysfunction in men with Type 2 diabetes. Therefore, cooking a hamburger with a polyphenol-rich spice mixture may lead to potential cardiovascular benefits in patients with Type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…When participants engaged in a 25 min long battery of performance-based, standardized, stressor tasks during the postmeal period, this beneficial effect of spices was not evident. We have previously demonstrated the triglyceride lowering effect of spices in a small pilot study [ 15 ], while others found no effect [ 16 ]. This latter, null finding was likely due to the minor postprandial change in triglycerides induced by the test meal that contained ~25 g of fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When participants engaged in a 25 min long battery of performance-based, standardized, stressor tasks during the postmeal period, this beneficial effect of spices was not evident. We have previously demonstrated the triglyceride lowering effect of spices in a small pilot study [ 15 ], while others found no effect [ 16 ]. This latter, null finding was likely due to the minor postprandial change in triglycerides induced by the test meal that contained ~25 g of fat.…”
Section: Discussionmentioning
confidence: 99%
“…However, replication of this finding is important, given the small sample size of the pilot study. In addition, a recent study testing a similar spice blend showed no effect on ppTG in adults with type 2 diabetes [ 16 ]. The present study was designed to assess the efficacy of a culinary spice blend to blunt ppTG following a high fat meal in healthy, but overweight/obese adults.…”
Section: Introductionmentioning
confidence: 99%
“…6 Postprandial lipid oxidation refers to the susceptibility of lipids or fats to oxidation after eating a meal; it is an important area of research because humans eat throughout the day and seldom fast for long periods. 6 Postprandial lipid oxidation refers to the susceptibility of lipids or fats to oxidation after eating a meal; it is an important area of research because humans eat throughout the day and seldom fast for long periods.…”
Section: Spice Mixture Added To Hamburger Improved Endothelial Dysfunmentioning
confidence: 99%
“…We previously demonstrated that a mixture of spices added to hamburger meat during cooking not only decreased malondialdehyde (MDA) in the meat, but healthy volunteers consuming hamburgers cooked with spices excreted significantly less urinary malondialdehyde, a marker of oxidative damage, compared to volunteers ingesting hamburgers cooked without added spices (Li et al 2010 , 2013 ). The spice mix contained ground cloves (4.3%), cinnamon (4.3%), Mediterranean oregano (26.2%), rosemary (4.3%), ginger (10.9%), black pepper (6.5%), paprika (30.4%) and garlic powder (13.0%) (Li et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%